Connecting to Compete 2016 : Trade Logistics in the Global Economy--The Logistics Performance Index and Its Indicators - Arvis, Jean-François; Saslavsky, Daniel; Ojala, Lauri; Shepherd, Ben; Busch, Christina; Raj, Anasuya; Naula, Tapio (World Bank, Washington, DC, 2016)
The LPI has provided valuable information for policy makers, traders, and other stakeholders, including researchers and academics, on the role of logistics for growth and the policies needed to support logistics in areas such as infrastructure planning, service provision, and crossborder trade and transport facilitation. The results of Connecting to Compete 2016 point to Germany as the best performing country, with an LPI score of 4.23, and Syria as the lowest, with a score of 1.60 (equivalent to 19 percent of Germany’s score on a scale from 1 to 5). The converging trend between the top and worst performers that appeared in the previous LPI surveys (2007, 2010, 2012, and 2014) seems to have slightly reversed. The average scores in each quintile reveal that the gap between the top 2 quintiles and the countries at the bottom in performance is widening again.